The risk of various types of cardiovascular diseases in mutation positive familial hypercholesterolemia; a review - Hovland, Anders; Mundal, Liv J.; Veierød, Marit B.; Holven, Kirsten B.; Bogsrud, Martin Prøven; Tell, Grethe S.; Leren, Trond P.; Retterstøl, Kjetil (Frontiers in Genetics, 2022)
Familial hypercholesterolemia (FH) is a common, inherited disease characterized by high levels of low-density lipoprotein Cholesterol (LDL-C) from birth. Any diseases associated with increased LDL-C levels including atherosclerotic cardiovascular diseases (ASCVDs) would be expected to be overrepresented among FH patients. There are several clinical scoring systems aiming to diagnose FH, however; most individuals who meet the clinical criteria for a FH diagnosis do not have a mutation causing FH. In this review, we aim to summarize the literature on the risk for the various forms of ASCVD in subjects with a proven FH-mutation (FH+). We searched for studies on FH+ and cardiovascular diseases and also included our and other groups published papers on FH+ on a wide range of cardiovascular and other diseases of the heart and vessels. FH+ patients are at a markedly increased risk of a broad range of ASCVD. Acute myocardial infarction (AMI) is the most common in absolute numbers, but also aortic valve stenosis is by far associated with the highest excess risk. Per thousand patients, we observed 3.6 incident AMI per year compared to 1.9 incident aortic valve stenosis, however, standardized incidence ratio (SIR) for incident AMI was 2.3 compared to 7.9 for incident aortic valve stenosis. Further, occurrence of ischemic stroke seems not to be associated with increased risk in FH+. Clinicians should be aware of the excess risk of almost all kind of ASCVD in FH+, and the neutral risk of stroke need to be studied further in FH+ patients.